Assessment of a novel rapid-hardening mortar incorporating waste basic oxygen furnace slag: mechanical behavior, durability, and environmental impact - Omur, Tarik; Miyan, Nausad; Ozkan, Hakan; Kabay, Nihat (TAYLOR & FRANCIS LTD, 2025)
This study investigates the potential of alkali-activated rapid-hardening mortars (RHMs) utilizing basic oxygen furnace slag (BOFS) and ground granulated blast furnace slag (GBS) as precursors. BOFS enhances early-age strength, with compressive strength increasing from 3.3 MPa to 5.8 MPa at 3h and from 5.7 MPa to 7.9 MPa at 6h, achieving up to 76% and 39% improvement, respectively. However, excessive BOFS (>= 40%) compromises long-term strength, with 28-day strength reducing from 64.7 MPa (0% BOFS) to 9.4 MPa (100% BOFS). Optimal performance was observed for 20% to 40% BOFS substitution, ensuring ASTM C928 compliance for rapid repair applications. Pore and microstructural analysis showed that moderate BOFS content refines pore structure and improves durability. However, higher BOFS levels increased porosity, elevated shrinkage (up to 51.5% compared to the reference), and reduced long-term strength. The environmental assessment revealed reduced carbon emissions, with BOFS-based RHMs producing 220.5 to 294.7 kgCO2/m3-nearly 50% lower than cement mortars.
Keywords: Alkali-activated material; rapid hardening mortar; basic oxygen furnace slag; compressive strength; durability; life cycle assessment; DRYING SHRINKAGE; ALKALINE ACTIVATION; WATER-ABSORPTION; HYDRATION; STRENGTH; CEMENT; MICROSTRUCTURE; CONCRETE; POWDER; Construction & Building Technology; Science & Technology - Other Topics; Materials Science